PERANAN KELOMPOK TANI TERHADAP PENDAPATAN USAHATANI PADI SAWAH ( Oriza sativa L ) - Ifan Hatibi; Hertasning Yatim; Ruslan A Zaenuddin (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Rice as the food commodity has a very high strategic value, so that serious handing is needed is its productiivity.The improvement efforts large role of the govenment in the management of food commodities, especially rice.This study aims to determine the role of padi sawah Farmers’ groups is Lembah Tompotika Village, Bualemo District. To find out the amount of rice farming income in Lembah Tompotika Village, Bualemo District, from march to May 2021. The types of data used is primary and secndary data. Used Likert Scale Analysis The level of the role of tarmer groups can be measured using a Likert Scale, ehich describers the five indicators into several question items that have been prepared in the questionnaire and each question item is given a score according to the respondent’s choice. Income Analysis to find out rice farming income leved. The role of farmer groups in disseminating information with a higt category 71,2%, Providing facilities and production facilities with a high category of 75,2%, Planning activities with a very high category 88,8, five farming technologi with a hight category of 70,4, Cooperating with KUD institutions with a very hight category 95%. This shoes that the role of farmer groups in the 5 indicators plays an infortant role in income The income obtained by famers in the valley of tompotika Village, Bualemo District,which is obtained from the result of subtracting the total revenue (TR) of Rp 56.000,000.00 with the total cost (TC) of Rp 12,526,100.00, then the income = TR-TC is Rp 43,473,900.00. This is this means that lowland rice farming can stiil be cultivated or developed by farmers in Lembah Tompotika Village, BualemoDistrict, Banggai Regency, because the amount of income earned is stiil quite high.